Systematic Review and Meta-Analysis of Unconventional Perfusion Flaps in Clinical Practice - Casal, D (2022)
Background: Although unconventional perfusion flaps have been in clinical use since 1975, many surgeons are still deterred from using them, because of some reports of high necrosis rates. Methods: The authors performed a systematic review and meta-analysis of all articles written in English, French, German, Spanish, and Portuguese on the clinical use of unconventional perfusion flaps and indexed to PubMed from 1975 until July 15, 2015. Results: A total of 134 studies and 1445 patients were analyzed. The estimated survival rate of unconventional perfusion flaps was 89.5 percent (95 percent CI, 87.3 to 91.3 percent; p < 0.001). Ninety-two percent of unconventional perfusion flaps (95 percent CI, 89.9 to 93.7 percent; p < 0.001) presented complete or nearly complete survival. Most defects mandating unconventional perfusion flap reconstruction were caused by trauma (63.6 percent), especially of the hand and fingers (75.1 percent). The main complication of all types of flaps was a variable degree of necrosis (7.5 percent of all unconventional perfusion flaps presented marginal necrosis; 9.2 percent and 5.5 percent had significant and complete necrosis, respectively). There was a positive correlation between the rate of postoperative infection and the need for a new flap (Pearson coefficient, 0.405; p = 0.001). Flaps used to reconstruct the upper limb showed better survival than those transferred to the head and neck or to the lower limb (p < 0.001). Conclusion: Unconventional perfusion flaps show high survival rates and should probably be used more liberally, particularly in the realm of upper limb reconstruction. Clinical question/level of evidence: Therapeutic, V.